Review Essay: Capitalism, Inequality, and Meritocracy. Issue 2 (2020) - Bird, Colin
Abstract : Trying to judge capitalism and the social forms it has brought into being is a bit like asking adolescents to assess puberty as they are going through it. We instinctively recognize that we are living through a particular phase in our development; we notice an expansion of our powers as well as recurrent problems attending their exercise; we find our concerns, attention, and aspirations reoriented in various ways; and our attitudes to our situation swing wildly between optimism, nostalgia, rebellion, exhilaration, and dejection. Similarly, we are uncertain about which aspects of market-saturated social arrangements will turn out to be temporary aberrations rather than permanent fixtures, and wonder constantly whether we must simply learn to cope with their effects, or should instead actively strive to master them. Above all, like the anxieties of adolescence, our assessments are haunted by vanity: Should we be proud or ashamed of what we are becoming and making of ourselves? Since, in one way or another, they address the adequacy of capitalist social forms, the three books under discussion all give voice, and in some cases respond, to these anxieties. They nonetheless belong to very different genres.